Local Chinese dialects and toponymy of Chinese Streets in Sibu, Sarawak - Ling Yann, Wong (JALA Publication, 2022)
This paper aims to explore the categories, structural formation, lexicon and Romanised characteristics of nomenclature of Chinese streets in Sibu, Sarawak, in Malaysia. Sibu is the third biggest city in Sarawak, and has been labelled ‘New Foochow’ or ‘Little Foochow.’ The Foochow community in Sibu is one of the state’s largest ethnicities. As such, the Foochow culture and dialect play an important role in developing the history of Sibu. Consequently, one significant influence of the Foochow community, and its culture and dialect towards the history of Sibu is the naming of the city streets in Chinese. This study adopts a descriptive and categorical qualitative research methodology to collect and analyse research data on Chinese names of streets in Sibu, Sarawak, Malaysia, and hence employs a historical and comparative study in order to describe the categories, structure, syllabic qualities, and Romanisation of the names of Chinese roads, streets, and lanes in Sibu.